Microsatellite and trinucleotide repeat expansion diseases - Rubinsztein, David C. (Henry Stewart Talks, 2020)
Mendelian neurodegenerative diseases are caused by repeat expansions, The mutation can result in gain-of-function or loss-of-function, Fragile X syndrome, Myotonic dystrophy, Huntington’s disease, Friedrich’s ataxia, C9orf72